KAJIAN PERANAN KAYU LAHAN MILIK RAKYAT TERHADAP PENDAPATAN RUMAH TANGGA PENGELOLANYA ( Studi Kasus di Kecamatan Kare Kabupaten Madiun) - Setyo Martono, Djoko; Sulasno, Sulasno (JURNAL AGRI-TEK, 2014)
Timber income people so far only considered as a complement of the total income that is less serious and usually managers in maintenance when compared to the maintenance of agricultural crops. Along with the price of wood then the public got interested and serious about the people timber plants that mostly dominated by teak as carpentry, industrial raw materials and energy sources both in the countryside and in the cities in Java purpose of this study was to determine the role of production of timber from land owned by the people of the total revenue for the managers, especially in the area of research studies conducted on land owned by the village folk and Randualas Kuwiran Kare District of Madison County in April to May 2014 for data retrieval lapangannya.Metode used in this research is descriptive method quantitative. The results showed that the production potential of community forest management varies depending on the shape of the plant and the type of crops grown on his land. Average potential timber forest land owned by the people in the District of Kare at 83.1884 m3 / ha, with an average of greatest potential in Hamlet Dawung with an average potential of 109.7928 m3 / ha and the average potential in the smallest hamlet Kuwiran with average potential 50.7758 m3 / ha. While the average estimated annual increment of 11.2516 m3 / ha / year. Revenue contribution from timber land owned by the people ranks second only to other income of the farmer respondents ie 25% of the total income of farmers as managers. Carpentry needs can be fulfilled at the sites of potential timber owned by the farmer managers.Keywords: Roles, Land Belongs to the People, Revenue